REDUPLIKASI BAHASA INGGRIS DAN BAHASA TALAUD (SUATU ANALISIS KONTRASTIF) - Maniara, Raegina Anggreani (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT This study is an attempt to describe and analyze the English and Talaud language specifying on the process of reduplication and the contrast of both languages to find the similarities differences interms of forms analysing.state that reduplication is defined as the repetition of all or part of a morpheme to express a morphological category. It is a term in morphology for a process of repetition whereby the form of a prefix/suffix reflects certain phonological characteristics of the root (Jensen 1990:68 and CrystalÂ 2008:407) The English data were collected from several English books, dictionary, thesis, related theories from library,internet, whereas the Talaud data were collected from informants and internet. The data were then analyzed descriptively using Jensen (1990), Crystal (2008), Sapir (1921), Katamba (2009), Quirk and Greenbaum (1973), Kridalaksana (2009). Theoretically this research is going to give a contibution in morphological analysis especially on reduplication, for development of linguistics at the faculty of Cultural Sience Sam Ratulangi University. The result of this investigation shows that reduplication in English and Talaud have some similarities and differences. The similarities are that both languages in form full reduplication, but limited to some class word. The difference be found in form, function, in English has full reduplication with phoneme variation whereas Talaud language have to shape full reduplication, partial reduplication, and reduplication with affix combination. . Keywords: Reduplication, English and Talaud Language, Contrastive Analysis